HOW BANK SERVICE INNOVATION AFFECTS THE VALUE OF CUSTOMER EXPERIENCE AND DECISION TO BE LOYAL - Ni Rai Artini; Aripin, Zaenal Aripin; Ngurah Made Novianha Pynatih (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2023)
In light of technological advancements and heightened competition in banking, institutions are adopting service innovations to retain clientele. Yet, the impact of such innovations on customer experience value and loyalty remains underexplored. This study aims to scrutinize the relationship between bank service innovation, customer experience value, and loyalty decisions. Additionally, it seeks to identify pivotal factors within service innovation that shape customer experience value and loyalty choices. Employing a literature study encompassing previous research, articles, and books on bank service innovation, customer experience, and loyalty, the research sourced reliable data to comprehensively comprehend the subject. Findings highlight the positive influence of bank service innovation on customer experience value. Greater innovation levels correlate with elevated experiential value for customers. Moreover, customer experience value significantly impacts decisions to remain loyal. Key determinants such as service reliability, user-friendliness, and interaction quality sway both customer experience value and loyalty decisions. This research adds vital insights into how bank service innovations mold customer experience value and loyalty determinations. The outcomes provide guidance for banks to implement effective service innovations, thereby enriching customer experiences and fortifying loyalty.